PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MENCARI PASANGAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI KELAS VIII DI MTs âAISYIYAH PALEMBANG - Firdaus, Firdaus; Syarifah, Syarifah; Handayani2, Tuti (Fakultas Tarbiyah dan Keguruan,Universitas Islam Negeri, 2015)
This research is about âThe Effect of Application Cooperative Learning Model Technique Make a Match Result Studying Biology in MTs âAisyiyah Palembangâ. Based on initial observasion of the result obtained from the value of studying biology teacher that only 40% of students who achieved the minimum completeness 70. This is a problem and need to be treated with the uses of appropriate learning strategies so that these problem can be solved. In this process of learning a lot of communication is expected to occur toward the expected activity and creativity. With that in mind it was attempted to explore the uses of a cooperative learning model technique make a match. Through cooperative learning model is expected to improve students learning outcomes. This research carried on 28 October until 1st November 2013. This study aims to determine the learning outcomes of students taught with cooperative learning technique make a match. Sampling of this study amounted to 80 people in the class VIIIA and VIIIB class as the subject of MTs âAisyiyah Palembang. Data retrieval result by using the instrument of learning achievement test (24 items). Data analysis using t-test and obtained tcount 3.98 at 5% level and obtained ttable 1.99, then tcount> ttable, so it can be concluded taught using cooperative learning technique make a match have a significant influence on student learning outcomes eighth grade in the subject matter of biology at MTs âAisyiyah.